Northeast Siberian Permafrost Ice‐Wedge Stable Isotopes Depict Pronounced Last Glacial Maximum Winter Cooling. Issue 7 (9th April 2021) - Wetterich, S.; Meyer, H.; Fritz, M.; Mollenhauer, G.; Rethemeyer, J.; Kizyakov, A.; Schirrmeister, L.; Opel, T.
Abstract: Stable isotopes (δ 18 O, δD) of wedge ice hold potential to reconstruct past winter climate conditions. Here, we present records of the marine isotope stages (MIS) 3 and 2 including the last Glacial maximum (LGM) from Bol'shoy Lyakhovsky Island (NE Siberia). MIS 3 wedge ice dated from 52 to 40 Kyr b2k varies between −32 and −29‰ in δ 18 O. Colder LGM conditions are implied by δ 18 O of −37‰ around 25 Kyr b2k. Similar Deuterium excess values indicate comparable moisture sources during MIS 3 and MIS 2. Regional LGM climate reconstructions depend on the seasonal resolution of the proxies and model simulations. Our wedge‐ice record reflects coldest winters during global minima in atmospheric CO2 and sea level. The extreme LGM winter cooling is not represented in model projections of global LGM climate where West Beringia shows noticeably little cooling or even warming in mean annual temperatures compared to the late Holocene. Plain Language Summary: The geochemical signature of stable isotopes of permafrost ground ice preserves information about past climate conditions. A common type of ground ice is ice wedges that form by the freezing of snowmelt in frost cracks developed on the ground and grow over time in width and length. Winter temperatures, and the type (snow or rain) and origin (regional moisture source) of winter precipitation largely control the stable isotope characteristics of oxygen and hydrogen in ice wedges. Here, we study the stable isotope composition of ice wedges from the last glacial period in northeastern Siberia. Plant and animal fossils that were found within the ice and in the surrounding frozen ground provide age control spanning from more than 50 to 24 thousand years ago when the ice wedges grew. The coldest winter conditions are inferred from a New Siberian Island ice‐wedge site as indicated by the lowest stable isotope values of all our sampled ice wedges at times, corresponding to the last Glacial maximum around 25 thousand years ago. Key Points: Pronounced west Beringian MIS 3 to MIS 2 winter cooling delineated in wedge‐ice stable isotope signatures Coldest winters reflected by exceptionally depleted values of −37.4 ± 0.4‰ in δ 18 O and −292 ± 3‰ in δD in LGM wedge ice LGM wedge ice directly radiocarbon‐dated to 25, 890 and 23, 980 yr b2k